Perancangan Aplikasi Email Menggunakan Algoritma Caesar CIPHER dan Base64 - Dwi Nurani (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
Send news or documents into individual or group communication media. The nature of news or documents are also used to be very secret. Increasingly sophisticated technology makes it increasingly easy to send a message or document. For example, in the advancement of the internet many parties that provide email management services, from sending or receiving also in terms of archiving. Convenience offered technology is not no risk. News or documents sent over the Internet are vulnerable to crime. In order for news or document can be up to the recipient safely and intact then takes the role of cryptography. Cryptography is the science to encrypt a message to make it more secure. In this study, using algorithms and Base64 Cipher Caesar. Caesar algorithm is an algorithm that is old and easily. While Base64 using ASCII format. So that the two algorithms can be used as it is complex. As a result, the security level is higher than not using cryptography. The encryption process and decryption not complicated and does not require a long time. If there are those who are not responsible to know the content of news or documents then he should know the key to reading and ensured key that only the sender and receiver know.